Development Model of Rice Supply Chain Management to Ensure Self-Sufficiency and Food Security - Yuntawati Fristin; Fajar Supanto (Jurnal Bisnis dan Manajemen, 2021)
The objectives of this study cover not only the availability of information about potential rice production, the actual information of rice supply chain system, and the concept and strategy of the rice supply chain management but also the formulation of effective and efficient measures to increase the rice distribution chain linkages in Malang Regency. The study design is a combination of descriptive and policy research unit by applying analysis of Rice Milling Unit (RMU) Entrepreneurs, Wholesalers and Retailers, Farmers and stakeholders concerned. The sampling was carried out by non-probability sampling method. The first sampling used purposive sampling method, and then the snowballing sampling method. The data comprised two types of data, primary and secondary data. The primary data were obtained through direct observation and interviews. The secondary data were obtained through literary searches. The data processing was done by the framework of the Food Supply Chain Networking (FSCN). The results indicated that Malang Regency has successfully contributed to the increase of national unhulled rice production. Furthermore, every year Malang Regency has a surplus of rice. The rice distribution pattern consists of the rice traders, millers, wholesalers, Bulog Malang Sub Division, and retailers. The distribution pattern of rice in Malang Regency has five channels of trade distribution system. In general, the market structure of unhulled rice / rice in Malang Regency is competitive. It is characterized by a number of participants of the market not only at the village, district but Regency as well. The distribution pattern has been established and supported by adequate infrastructure. Moreover, the distribution is quite smooth without encountering any major obstacles. The results of this study provide interesting findings because the rice produced by farmers in Malang Regency is mostly sold outside Malang Regency. Most of the people of Malang Regency consume rice from other areas because the price is cheaper than the rice of Malang Regency farmers. This condition should improve the welfare of farmers because the rice produced is of premium quality and is more expensive, but market conditions make this expectation difficult to fulfill because the price is affordable at RMU. To Strengthen the supply chain management of rice, it is needed the growth and strengthening of the system either upstream or downstream of economy through institution of the village. The institution has a bridging function for both the interests and needs of the community. The government should provide sufficient funds through Bulog to buy all rice produced by farmers at a price that supports farmers in making a profit, then distribute it to the community at a price affordable to the purchasing power.